PENGELOLAAN ASET TANAH DAN BANGUNAN PADA KABUPATEN TABALONG - , ARBANI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The aims of the study are measuring the perception of manager/user of local government good (land and building) at Tabalong Regency. Implementation asset management by Tabalong Local Government. The study was description with quantitative approach using IPA (importance-performance analysis) to determined asset management in Tabalong Local Government. Data collected using purposive sampling that take managerial and user in Tabalong Local Government. Questionnaire was distributed to 33 respondens from 22 local government unit in Tabalong Regency. The results shows manager and user of local government good in Tabalong Regency more pointed in land and building monitoring and controlling. This policy was taken because land and buildings that havenât optimize and no clarify in their status. Management of land and buildings in Tabalong Regency havenât fully expectation. So many asset of idle lands and no clear status still become a home work for managerial in Tabalong Local Government. Another problem is the buildings belong to Tabalong Local Government and still unoptimize in their usage.